Leading indicators in a globalised world - Ferdinand Fichtner; Rasmus Rüffer; Bernd Schnatz (European Central Bank (ECB), 2009)
Using OECD composite leading indicators (CLI), we assess empirically whether the ability of the country- specific CLIs to predict economic activity has diminished in recent years, e.g. due to rapid advances in globalisation. Overall, we find evidence that the CLI encompasses useful information for forecasting industrial production, particularly over horizons of four to eight months ahead. The evidence is particularly strong when taking cointegration relationships into account. At the same time, we find indications that the forecast accuracy has declined over time for several countries. Augmenting the country-specific CLI with a leading indicator of the external environment and employing forecast combination techniques improves the forecast performance for several economies. Over time, the increasing importance of international dependencies is documented by relative performance gains of the extended model for selected countries.
Keywords: C53; E32; E37; F47; 330; business cycle; forecast comparison; Globalisation; Leading Indicator; Structural change; Wirtschaftsindikator; Prognoseverfahren; Globalisierung; Industrieproduktion; OECD-Staaten